Re: HSC 2015 4U Marathon
NEXT QUESTION
Sorry, can't tell if the old one was finished.
http://imgur.com/k3Xgd2N
This was taken from the final page of my complex numbers test
It suffices to show all the results assuming
![](https://latex.codecogs.com/png.latex?\bg_white \theta \in \left [ -\pi,\pi \right ] )
, due to the periodicity and powers of the functions in question. So assume
![](https://latex.codecogs.com/png.latex?\bg_white \theta \in [ -\pi,\pi] )
.
(i)
![](https://latex.codecogs.com/png.latex?\bg_white =\sqrt{2+ 2\cos \theta })
(since sin
2 t + cos
2 t = 1 ∀
t ∈ ℝ)
![](https://latex.codecogs.com/png.latex?\bg_white =\sqrt{2(1+\cos \theta )})
.
If cos
θ ≠ -1, ℝe(1+
z) = 1+cos
θ > 1+(-1) = 0, so that
![](https://latex.codecogs.com/png.latex?\bg_white =\tan ^{-1}\left (\tan \frac{\theta}{2} \right ))
, using the identity
![](https://latex.codecogs.com/png.latex?\bg_white \frac{\sin \theta}{1+\cos \theta}=\tan \frac{\theta}{2})
for cos
θ ≠ -1 (this can be proved using
t-formulae or half-angle identities)
![](https://latex.codecogs.com/png.latex?\bg_white =\frac{\theta}{2})
, since
![](https://latex.codecogs.com/png.latex?\bg_white \frac{\theta}{2}\in\left ( -\frac{\pi}{2},\frac{\pi}{2} \right ))
, because we assumed that
![](https://latex.codecogs.com/png.latex?\bg_white \theta \in \left [ -\pi,\pi \right ] )
, and
![](https://latex.codecogs.com/png.latex?\bg_white \cos \theta \neq -1\Rightarrow \theta \neq \pm \pi)
.
So for cos
θ ≠ -1,
If cos
θ = -1 (that is, if
![](https://latex.codecogs.com/png.latex?\bg_white \theta = \pm \pi)
), then 1+
z = (1-1)+
i.sin(±π) = 0, and hence arg(1+
z) is undefined. However, the above formula still holds when 1+
z = 0 ⇔ cos
θ = -1.
So we have
![](https://latex.codecogs.com/png.latex?\bg_white 1+z=\sqrt{2(1+\cos\theta)}\left ( \cos\frac{\theta}{2}+i\sin\frac{\theta}{2} \right )\text{ }\forall \theta \in [-\pi,\pi] )
.
(ii) (1+
z)
4 = 1 + 4
z+6
z2 + 4
z3 +
z4, by the binomial theorem.
But by de Moivre's theorem and part (i),
![](https://latex.codecogs.com/png.latex?\bg_white =4\left (2\cos^2 \frac{\theta}{2}\right )^2 ( \cos2\theta+i\sin2\theta))
, since
![](https://latex.codecogs.com/png.latex?\bg_white \cos \theta = 2\cos^2\frac{\theta}{2}-1\Leftrightarrow 1+\cos \theta = 2\cos^2\frac{\theta}{2})
(from double angle identity for cosine)
![](https://latex.codecogs.com/png.latex?\bg_white =16\cos^4 \frac{\theta}{2}\left ( \cos 2\theta+i\sin 2\theta \right ))
.
Equating both expressions for (1+
z)
4,
The identity required to be shown follows from taking real parts of the above equation and recalling that by de Moivre's theorem,
![](https://latex.codecogs.com/png.latex?\bg_white \Re (z^k)=\cos k\theta )
and that 'real part' is a linear operator, so that the real part of a sum is the sum of real parts.
The second expression is given by
![](https://latex.codecogs.com/png.latex?\bg_white 4\sin \theta + 6\sin 2\theta + 4\sin 3\theta+\sin 4\theta=16\cos^4 \left (\frac{\theta}{2}\right )\sin 2\theta \text{ }\mathbf{(Equation \text{ }(\ast))})
, which follows in a similar way, this time by taking imaginary parts.
(iii)
The first identity follows by dividing Equation (*) by the identity required to prove in part (ii) (and recalling that
![](https://latex.codecogs.com/png.latex?\bg_white \tan X = \frac{\sin X}{\cos X})
), for
![](https://latex.codecogs.com/png.latex?\bg_white 16\cos^4 \frac{\theta}{2}\neq 0 \Leftrightarrow \frac{\theta}{2}\neq\pm \frac{\pi}{2}\Leftrightarrow \theta \neq \pm \pi)
(so that the factor of
![](https://latex.codecogs.com/png.latex?\bg_white 16\cos^4 \frac{\theta}{2} )
can be cancelled from the numerator and denominator).
For the second identity, we rearrange the identities proven in part (ii) to get:
and
![](https://latex.codecogs.com/png.latex?\bg_white 1 + 4\cos \theta + 4\cos 3\theta + \cos4\theta = 16\cos^4\left ( \frac{\theta}{2}\right)\cos 2\theta - 6\cos2\theta = \left ( 16\cos^4 \frac{\theta}{2} -6 \right )\cos 2\theta \text{ (2)})
.
The identity follows upon dividing (1) by (2), provided that
![](https://latex.codecogs.com/png.latex?\bg_white 16\cos ^4 \frac{\theta}{2} - 6\neq 0 )
.